Editorial [Hot Topic: Protein Targets in the Treatment of Cancers (Guest Editor: Sabbir Ahmed)] - Ahmed, Sabbir (Anti-Cancer Agents in Medicinal Chemistry, 2009)
The use of compounds to affect the activity of proteins (both enzymes and receptors) is still under extensive consideration in the development of novel anti-tumour agents. In this issue, we consider a number of targets which have been (and continue to be) under investigation and which have shown therapeutic/clinical potential in the treatment of cancers. However, due to the nature of the area, it is difficult to undertake an extensive coverage of the use of small molecules against proteins within a journal issue, as such, the authors have attempted to provide the reader with a background into the general approach in the treatment of cancers through the use of protein modulators. The first paper by Aidoo-Gyamfi et al. covers one of the novel areas which have been shown to have clinical potential, namely the use of inhibitors of estrone sulfatase in the treatment of hormone-dependent breast cancer. The paper gives an overview of the area as well as discussing some compounds (for example, STX-213) which possess the potential to enter the clinic. The paper by Owen discusses another enzyme target within the steroidal cascade, namely, 17α-hydroxylase/17, 20-lyase, which has mainly been targeted in the treatment of androgen-dependent prostate cancer. A number of compounds have been targeted at this enzyme which has shown real potential, for example, abiraterone acetate has shown real promise in clinical trials, in particular, against refractory prostate cancer. This enzyme also has potential use in the treatment of estrogen-dependent breast cancer since it is a pivotal enzyme in the biosynthesis of the sex steroids. Indeed, 17α- hydroxylase/17, 20-lyase results in the biosynthesis of androgens which can therefore lead, via the action of the enzyme aromatase, to the biosynthesis of estrogens, the topic of the third paper by Banting and Ahmed. This paper therefore covers an enzyme which has shown real clinical significance through the emergence of drugs such as anastrozole and letrozole in the treatment of estrogen-dependent breast cancer. In his paper, Poirier discusses the inhibition of the enzyme 17β-hydroxysteroid dehydrogenase as this family of enzymes is involved in the transformation of weaker steroids (for example androstenedione or estrone) into the more potent sex steroids (for example testosterone and estradiol respectively) and vice versa. This enzyme has only recently become of importance since it was previously assumed to be a weak target due to non-specificity of the compounds since there are some 15 types of this enzyme which have been reported to exist. However, as discussed, a number of compounds have been shown to possess specificity and this enzyme has become a major target in the treatment of both hormone-dependent breast and prostate cancers. As such, these four papers represent the majority of the efforts directed towards the disruption of the steroidal cascade and therefore the treatment of hormone-dependent cancers. In the paper by Marson, the targeting of histone deacetylase is discussed with an overview of the different types of compound used to target this enzyme; the paper also discusses the potential use of inhibitors of this enzyme against refractory cancer. The paper by Winum et al. gives an extensive overview of the use of inhibitors against carbonic anhydrase, in particular, against isozyme IX of carbonic anhydrase. This isozyme has been implicated in the control of cell proliferation and cellular malignant transformation, indeed; its expression has been shown to be restricted in normal tissues but has been closely associated with different types of tumours, especially hypoxic solid tumours. Finally, Loew et al. discuss the targeting of epidermal growth factor receptor since it has been shown to be dysregulated in various tumour types including breast cancer and glioblastoma multiforme (GBM). In particular, treatments against GBM are discussed; a disease which is associated with a median survival of only 40 to 60 weeks from diagnosis, as such, this paper gives an insight into the achievements and challenges associated in the treatment of GBM. I believe, therefore, that this special issue will successfully introduce the reader to the challenges and achievements associated with a small number of targets which are under consideration in the treatment of various cancers.